Bimbingan Pembuatan Proposal Penelitian Tindakan Kelas Bagi Guru Peserta MGMP Matematika Kota Banjarmasin - Hidayah Ansori; Sutarto Hadi; Rizki Amalia; Ahmad Haekal Syahrian (Carmin: Journal of Community Service, 2022)
The teacher factor is the first and foremost subsystem in improving education quality. Without professional teachers, it is impossible for an education system to achieve the expected results. Therefore, the main prerequisite that must be met for the teaching and learning process to optimize learning outcomes is the availability of teachers with qualifications and competencies who can meet the demands of their duties. Teacher competencies are described in the lesson plans made. Currently, the lesson plan is made simpler: one page consisting of learning objectives, learning steps, and learning assessments. Lesson plans will be made through an online word-processing application. This service activity aims to teach teachers at the Mathematics MGMP of Barito Kuala Junior High School to make one-page lesson plans using an online word processor. The output of this training is an application to construct lesson plans and articles submitted to national scientific journals. The training is conducted online. Coaching will also be online via Zoom, email, and WhatsApp. Training is carried out 3-4 hours daily, once a week. The implementation is estimated at three times online meetings. After that, there was guidance twice regarding the tasks given in the training. The activity went well. The use of an online word processor to create a one-page. Lesson plans can be used effectively and efficiently during the current pandemic